2019
DOI: 10.1016/j.isci.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The FG Loop of PD-1 Serves as a “Hotspot” for Therapeutic Monoclonal Antibodies in Tumor Immune Checkpoint Therapy

Abstract: Summary Programmed cell death 1 (PD-1)/PD-1 ligand-1 (PD-L1)-blocking monoclonal antibodies (mAbs) have taken center stage for tumor immune checkpoint therapy. Identification of the “hotspots” on PD-1 for mAbs will help to develop next-generation oral deliverable agents with long-lasting efficacy. Here, we identified two PD-1-targeting mAbs, GY-5 and GY-14, with PD-1/PD-L1-blocking efficacy. Complex structural information revealed that both mAbs mainly bind to the FG loop of PD-1, which also contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…To date, five PD-1/Mab complex structures have been reported, including PD-1/nivolumab Fab 24,26 , PD-1/pembrolizumab Fab 2325 , and three other PD-1/Fabs 28,29 . Previous studies have shown that each PD-1 Mab exhibits different binding modality to PD-1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, five PD-1/Mab complex structures have been reported, including PD-1/nivolumab Fab 24,26 , PD-1/pembrolizumab Fab 2325 , and three other PD-1/Fabs 28,29 . Previous studies have shown that each PD-1 Mab exhibits different binding modality to PD-1.…”
Section: Resultsmentioning
confidence: 99%
“…In that study, authors demonstrated that N-glycosylation of PD-1 did not affect the binding affinity to nivolumab 26 . Recently, there were two reports about MAbs targeting PD-1, in which the binding modes were also glycosylation-independent 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, PD-1 glycosylation is not essential for PD-1/PD-L1 interaction. Structure studies revealed that PD-1 glycosylation sites are located away from PD-1/PD-L1–binding interface, suggesting that modifications of PD-1 glycosylation would not have direct influence on this interaction ( 23 ). Consistently, binding of the therapeutic blocking antibodies nivolumab and pembrolizumab to PD-1 was independent of PD-1 glycosylation ( 24 , 25 ).…”
Section: Expression Of Pd-1 and Its Ligandsmentioning
confidence: 99%
“…The FG and BC loops locate on the IgV domain. Previous studies showed that the FG loop (i.e., PD– 1 PRO130 and PD– 1 LYS131) is a binding site for PD-L1 as well as a “hot spot” for several immune checkpoint blockade monoclonal antibodies, such as GY-5 and GY-14 ( Zak et al, 2015 ; Liu and Liu, 2017 ; Chen et al, 2019a ). They clearly suggest a steric clash blockade mechanism of nivolumab.…”
Section: Introductionmentioning
confidence: 99%